Bimbingan Konseling Islam (al-Irsyad wa al-Tawjîh al-Islam) Berbasis Ilmu Dakwah - Isep Zainal Arifin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2008)
Bimbingan dan Konseling/Penyuluhan Islam (Islamic Guidance and Counseling) has been grown up in Dakwah Faculty rather than Tarbiyah. In fact, this disciplines more close to education field. This phenomenon caused the needs of Dakwah’s science basic to develop it. The methodology which uses are; Al-Thurûq al-Istinbâth, Al-Thurûq al-Iqtibâs, Al-Thurûq al-Istiqra,’Al-Jam’u Bayna Û’qûl al-Shafiyyah wa Nufûs al-Zakiyyah. In other or conventional counseling, BKI/BPI field become one of the methodology of counselling for all with psychology counseling as the the root, not pedagogic counseling.